Electricity Restructuring: What Has Worked, What Has Not, and What is Next - Jeff Lien (U.S. Department of Justice, Antitrust Division, Economic Analysis Group (EAG), 2008)
In the 1990s and early 2000s, a series of state and federal initiatives restructured electric markets. In many areas of the country generation was unbundled from transmission and distribution and competitive markets for energy generation were established. A decade has now passed since many of these market reforms were implemented, and increasing energy prices have re-focused attention on these reforms. In particular, commentators are blaming the reforms for the rising energy prices and, in several states, legislators are now considering re-imposing regulation. In this paper I discuss some successful features of industry restructuring, and consider areas where further reform may be warranted. It appears that market restructuring is now producing significant tangible benefits in the areas of the country where it has been most fully implemented. Calls for the reimposition of heavyhanded regulation should be resisted.
Keywords: L94; Q48; L51; 330; Energy; Electricity; Restructuring; Regulation